Pengaruh Disiplin Kerja dan Motivasi terhadap Kinerja Pegawai pada Kantor Kecamatan Sukmajaya Kota Depok - Mohammad Rofik; Ade Sri Mulyani (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The purpose of this study is to identify some significant effects of work discipline and motivation on the work performance of the deputy governor of the Sukmajaya district of the Depok city. The quantitative deskriptif method is the one used in this study. In this survey, 36 respondents who were dikantors of Sukmajaya Kota Depok were polled. Uji Validitas, Uju Realiabilitas, Uji Asumsi Klasik, Uji Normalitas, Uji Heteroskedastisitas, Uji Multikolinearitas, Uji Regresi Liner Berganda, Uji T (Parsial), Uji F (Stimultan), dan Uji Koefisien Determinasi sebagaian langit. Discipline-related discipline effects on work performance have a Thitung>TTabel ( 8,485 > 2,035 ) value; this is supported by a signifikativity of 0.000<0,05. This can be interpreted as meaning that Ho is dead and Ha is alive. The influence of motivation on employee work performance has a Thitung>TTabel (30,626 > 2,035) value; this may be explained by a signifikan 0,000<0,005. This can be seen as showing that Ho is tolak and Ha is diterima. The impact of work discipline and motivation simultaneously on the work-related kinerja is demonstrated by the Fhitung > 1141,097 > 4,13 and the signifikan 0,000 < 0,005 nilai koefisien determinasi (R2), which is around 0.986. This indicates that job satisfaction and work culture have a positive effect on employee work performance of around 0.986% or 98.6%, while the influence of other factors is responsible for the remaining 1.4% or 0.14 percent. It may be inferred from this that Ho is not the same as Ha.